Diagnosis of initial data to design a project model enabling the implementation of a business intelligence process for design and construction engineering companies in Cuba - García, Julio García; Macía, José A. (Revista Ingeniería de Construcción, 2010)
Business Intelligence Process during recent years have provided a growing number of companies all over the world with the ability to control internal and external environments and to create appropriate know-how for decision making processes; to provide a new Strategic Management orientation; to reduce the potential risk margin and to increase competitiveness. Cuba represents a leading sector of Design and Construction Engineering Companies for the implementation of this new Cuban Management and Business Administration System, seeking to diversify services in the national and international construction market. The purpose of this paper is to demonstrate the use of different tools, such as the expertise calculation index procedure, orientation and information interviews, surveys, category correlation and focus groups, which allowed the diagnosis of initial data situation on the project approach for the implementation of such a process. The most important outcomes were the definition of organization stages to be implemented, by means of a Business Intelligence Project, those elements that limit and facilitate the process. From these elements, an on-going scientific investigation design was created, counting with the cosponsorship from several universities and companies. Concrete results are expected to design a Business Intelligence Process for such companies and a Manual to guide researchers and executive staff involved in the improvement of similar entities of management.